6-gingerol promotes apoptosis of ovarian cancer cells through miR-506/Gli3 signaling pathway activation - Xiong, Jun; Wu, Hong-Hu; Jiang, Hui; Li, Huan; Tan, Xiao-Qing; He, Xiao-Ju; Cheng, Xue-Xin (Frontiers in Oncology, 2025)
PurposeGinger rhizomes have shown potential for promoting human health, including the prevention and treatment of cancer. Here, we investigated the anticancer activities of 6-gingerol and explored its mechanisms of action in ovarian cancer cells.MethodsSKOV3 ovarian cancer cells were treated with different concentrations of 6-gingerol. Clonogenic assays, Flow cytometry, and Western blotting were used to evaluate cell survival and apoptosis. RT-qPCR and transfection experiments were performed to assess the role of miR-506, and bioinformatics tools were used to identify Gli3 as a target gene.ResultsIn vitro, ovarian cancer cells underwent apoptosis following 6-gingerol treatment. 6-Gingerol suppressed Gli3 expression without affecting Bax, Bcl-2, or Bcl-xL levels. Low miR-506 expression was observed in ovarian cancer tissues, whereas 6-gingerol significantly promoted its expression. miR-506 directly suppressed Gli3 expression and induced apoptosis in SKOV3 cells.ConclusionsOur results indicate that gingerol promoted the upregulation of miR-506, leading to the induction of apoptosis in ovarian cancer cells. This study supports the potential of 6-gingerol-based therapy for ovarian malignancies.